The Role of Supply Chain Finance in Humanitarian Aid Relief : Literature Review - Mauliddina, Yasmin; Kasih, Puji Handayani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Humanitarian aid relief has been operational since the late 19th century, addressing development and disaster aid cases. The intricate relationship between humanitarian aid relief and the supply chain encompasses various stages, from securing funding to coordinating stakeholders. However, the volatile and uncertain nature of the field poses challenges such as corruption, prolonged funding gaps, and demands for accountability and visibility. This study highlights the critical role of funding and financing in the humanitarian supply chain, emphasizing the underdeveloped state of research on supply chain finance (SCF). The paper aims to investigate the integration of SCF into humanitarian aid relief, utilizing literature reviews from journals, papers, and reports.The findings reveal a correlation between SCF's essential elements—focused on liquidity/cash, operational activities, and engagement among actors. This research proposes a framework, how the humanitarian aid relief sequence and SCF theory should collaborate for effective humanitarian aid supply chain finance (HASCF) practices